1987
DOI: 10.1038/bjc.1987.107
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the incidence of the myelodysplastic syndrome and acute myeloid leukaemia following melphalan and cyclophosphamide treatment for myelomatosis

Abstract: The fact that treatment with cytotoxic agents can induce myelodysplasia (MDS) and acute myeloid leukaemia (AML) in patients suffering from cancer and from other diseases has now been thoroughly documented (Kyle et al., 1970;Reimer et al., 1977;Casciato & Scott, 1979;Berk et al., 1981;Coltman, 1982;Green et al., 1982;Pedersen-Bjergaard & Larsen, 1982;Boice et al., 1983;Boivin & Hutchinson, 1984;Lakhani, 1984). However, quantitative relationships with the dose and duration of treatment for different agents, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
6

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 19 publications
6
77
0
6
Order By: Relevance
“…We nevertheless consider that there exists a lower carcinogenicity for cyclophosphamide than for the other alkylating agents (mainly procarbazine and melphalan). This result is in agreement with published observations on survivors from ovarian cancers (Greene et al, 1986), and on survivors from myelomatosis (Cuzick et al, 1987), that melphalan is more leukaemogenic than cyclophosphamide.…”
Section: Discussionsupporting
confidence: 83%
“…We nevertheless consider that there exists a lower carcinogenicity for cyclophosphamide than for the other alkylating agents (mainly procarbazine and melphalan). This result is in agreement with published observations on survivors from ovarian cancers (Greene et al, 1986), and on survivors from myelomatosis (Cuzick et al, 1987), that melphalan is more leukaemogenic than cyclophosphamide.…”
Section: Discussionsupporting
confidence: 83%
“…1 So far, it has been shown that in vitro AML cells display an enhanced cholesterol metabolism. 2 Moreover, AML cells increase their cholesterol contents upon exposure to chemotherapeutic drugs, which may render them less …”
Section: Conflict Of Interestmentioning
confidence: 99%
“…1 Alkylating agents have long been considered to be part of the cause. [2][3][4][5] Some, but not all, smaller investigations have reported that higher cumulative melphalan dose and longer duration of melphalan therapy are associated with an increased risk of AML. 6,7 The role of nontreatmentrelated factors is largely unknown.…”
mentioning
confidence: 99%
“…6,[12][13][14] Many of these studies showed that the risk of t-MDS and t-AML increases with the cumulative dose of drug 4,5,7,9,10,13,14 and with patient age. 3,6,13,14 After the first reports of t-AML it was realized that in most of these patients the disease presents in a preleukemic stage as t-MDS with abrupt thrombocytopenia 2-5 years after start of therapy with alkylating agents.…”
Section: The 'Alkylator Types' Of Mds and Amlmentioning
confidence: 99%
“…The first cytostatic drugs shown to be leukemogenic were alkylating agents, administered as single agents 1,2,4,5,[8][9][10] or included in combination chemotherapy regimens, 3,7,11 primarily for multiple myeloma 1,3,10 and Hodgkin's disease. 6,[12][13][14] Many of these studies showed that the risk of t-MDS and t-AML increases with the cumulative dose of drug 4,5,7,9,10,13,14 and with patient age.…”
Section: The 'Alkylator Types' Of Mds and Amlmentioning
confidence: 99%